2016
DOI: 10.3233/jad-140669
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Protein Changes in Blood Plasma Associated with the Rate of Cognitive Decline in Alzheimer’s Disease

Abstract: Biomarkers of Alzheimer's disease (AD) progression are needed to support the development of urgently needed disease modifying drugs. We employed a SOMAscan assay for quantifying 1,001 proteins in blood samples from 90 AD subjects, 37 stable mild cognitive impaired (MCI) subjects, 39 MCI subjects converting to AD within a year and 69 controls at baseline and one year follow up. We used linear mixed effects models to identify proteins changing significantly over one year with the rate of cognitive decline, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 54 publications
(62 reference statements)
0
27
0
Order By: Relevance
“…Further to case-control studies, blood-based biomarker panels have been designed to estimate disease-related phenotypes, such as cognitive decline, brain atrophy and neocortical Aβ deposition. Inflammatory markers [50][51][52], as well as proteins associated with the complement cascade [53], have reported associations with cognitive performance, cognitive decline and clinical progression. Most of these contributions also examined the association of proteomic signatures with brain volumetry finding similar signatures [50,[54][55][56].…”
Section: Panels Of Blood-based Biomarker-associated Disease Phenotypesmentioning
confidence: 99%
“…Further to case-control studies, blood-based biomarker panels have been designed to estimate disease-related phenotypes, such as cognitive decline, brain atrophy and neocortical Aβ deposition. Inflammatory markers [50][51][52], as well as proteins associated with the complement cascade [53], have reported associations with cognitive performance, cognitive decline and clinical progression. Most of these contributions also examined the association of proteomic signatures with brain volumetry finding similar signatures [50,[54][55][56].…”
Section: Panels Of Blood-based Biomarker-associated Disease Phenotypesmentioning
confidence: 99%
“…More recently we have tested protein changes associated with rate of change and progression to dementia [ 55 ] in 235 subjects including 69 controls, 37 ‘stable’ MCI patients, 39 patients with MCI converting to AD within a year, and 90 AD patients. Results showed that twelve proteins were found to significantly associate with the rate of progression.…”
Section: Early Discovery Of Blood-based Biomarkers Of Alzheimer’s Dismentioning
confidence: 99%
“…Still, others have found no significant relationship [25,26]. Reduced plasma Ab has also been linked to poorer cognition [6,7,19,21,[27][28][29][30]. In addition, some studies have suggested that plasma levels of Ab42 and Ab40 are associated with the levels of cerebral Ab on positron emission tomography (PET), cerebrospinal fluid levels of Ab and tau, and AD-like brain atrophy [4,7,8,11,16,17,24,[31][32][33][34][35][36][37][38], while others have not seen such an association [25,39,40].…”
Section: Introductionmentioning
confidence: 99%